THERMOCHEMICAL CONVERSION OF FINE FRACTION SOLID FUEL INTO COMBUSTIBLE GAS - Скляренко, Євген; Воробйов, Леонід (SWorldJournal, 2024)
In the context of a shortage of energy resources and a constant increase in their prices, increasing the efficiency of their use and comprehensive savings, in particular through the use of low-grade fuels, is a priority area for the functioning of the co